Game Development to Introduce Indonesian Traditional Weapons using MDA Framework - Husniah, Lailatul; Fannani, Firdaus; Kholimi, Ali Sofyan; Kristanto, Andika Eko (Kinetik: Game Technology, Information System, Computer Network, Computing, Electronics, and Control, 2019)
It is unfortunate that more and more youths are less concerned and are not interested in acquainting and studying Indonesian traditional culture, especially concerning on traditional Indonesian weapons. This fact is noticed from data as collected from several bookstores including online bookstores which the number of books on traditional weapons originating from abroad as published in Indonesia has a significant comparison compared to books on traditional weapons from Indonesia, in a stagerring 1:7 comparisson. Therefore, it is necessary to develop a media that can generate interest in couriosly learning about Indonesian culture, especially when introducing traditional Indonesian weapons. This research was conducted to develop a media in the form of android games that can be applied for the introduction of Indonesian culture, especially traditional weapons. The employed method of game development is the MDA Framework. Evaluation was carried out by using the Playtesting Evaluation and Gameflow methods. The evaluation results related to the concentration of players during game playing presents that the game has given a lot of encouragement to players to play games in several aspects of: game graphics, game sound, game stories, gameplay, simple interfaces, and completion of missions and main objectives regarding traditional Indonesian weapons, trigerring the player interest in playing this game and to maintain their focus throughout the game. In overal, the evaluation results using playtesting evaluation and Gameflow test depicts that a rating above average with an overall rating of 3.61 (72.18%) and the game Mystical Weapon of Nusantara can be accommodated as a medium for the introduction of traditional Indonesian weapons as indicated by the probability of a t-test of 1,169x10-19 which is far below the value of α = 0.05. Thus, it is concluded that there is an improvement in user knowledge, as well as the value of respondent answer showing above the average, which is 3.83 (76.67%).